Students' Ethics Towards Teachers: Analysis of The Book Adāb Al-‘Ālim wa Al-Muta’allim By KH. Hasyim Asy’ari - Malikhah, Eniriatul; Muchlis, Ibnu (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Student ethics towards teachers is a fundamental aspect in the educational process, especially in the Islamic educational tradition. The relationship between students and teachers is not just an interaction of transferring knowledge, but also has deep moral and spiritual values. This article will explain the ethics of students towards teachers in the book Adāb al-‘Ālim wa al-Muta’allim by KH. Hasyim Asy’ari. This study uses a library research approach with primary and secondary data sources. The primary source in this study is the book Adāb al-‘Ālim wa al-Muta’allim by KH. Hasyim Asy’ari, while the secondary sources in this study are various articles related to student ethics towards teachers using descriptive analytical methods as data analysis techniques. The research findings show that the ethics of students towards teachers in the book Adab al-'Ālim wa al-Muta'allim include respecting and honoring teachers, tawadhu' or being humble, listening earnestly, not arguing or debating teachers harshly, maintaining morals and manners outside the classroom, asking permission and respecting the teacher's authority, practicing the knowledge taught, and praying for the teacher. Then the relevance includes building character and integrity, strengthening the relationship between teachers and students, maintaining the blessings of knowledge, teaching responsibility and discipline, forming a lifelong learning attitude, and avoiding individualistic attitudes and demeaning others.